Quantifying nitrate dynamics in a mesotrophic lake using triple oxygen isotopes as tracers. (19th January 2018) - Tsunogai, Urumu; Miyauchi, Takanori; Ohyama, Takuya; Komatsu, Daisuke D.; Ito, Masanori; Nakagawa, Fumiko
Abstract: Vertical distributions of both concentrations and stable isotopic compositions of nitrate, including the 17 O‐excesses (Δ 17 O), were determined four times during 1 yr within the mesotrophic water column of Lake Biwa in Japan. By using both the deposition rate of atmospheric nitrate onto the entire surface of the lake and the influx/efflux of both atmospheric and remineralized nitrate via streams reported in the literature, we quantified the annual dynamics of nitrate (gross production rate of nitrate through nitrification and gross metabolic rate of nitrate through assimilation and denitrification), together with their seasonal variations, based on the Δ 17 O method. The results revealed that 642 ± 113 Mmol (Mmol = 10 6 mol) of the remineralized nitrate was supplied into the water column through nitrification in the lake on an annual basis, while 810 ± 120 Mmol of nitrate was metabolized in the lake through assimilation and denitrification. In addition, it turns out that nitrification was active, not only in the hypolimnion, but also in the epilimnion and upper thermocline in this lake. Furthermore, the total metabolic rates of nitrate varied seasonally, with the highest rates in summer and the lowest in winter. Because the difference between the annual metabolic rate of nitrate estimated based on the Δ 17 O method and the annual assimilation rate of nitrate estimated based on the traditional 15 N incubation method was only 20%, we concluded that the Δ 17 O method reliably estimates the dynamics of nitrate in mesotrophic lakes.